New Relationships on the Northwest Frontier: Episodes in the Gitxsan and Witsuwit'en Encounter with Colonial Power - McCreary, Tyler Allan (2015)
This dissertation examines relationships between colonialism and Indigenous peoples that shape the development of extractive resources in Gitxsan and Witsuwit’en territories in Northwest British Columbia, Canada. I argue colonialism and Indigeneity are co-constituted. Theoretically, this dissertation brings an analysis of colonialism into conversation with Foucauldian understandings of sovereign, disciplinary, and governmental power. I begin by situating the relationship between colonialism and the Gitxsan and Witsuwit’en people historically, then transition to examine in greater detail the contemporary relations unfolding through the courts, traditional knowledge studies, resource governance, and education. I argue the Gitxsan and Witsuwit’en assertions of territory and jurisdiction in the Delgamuukw litigation exposed Indigenous traditions to new forms of colonial discipline and debasement but also induced new regimes of recognition and doctrines of reconciliation. Subsequently, Aboriginal traditional knowledge studies integrated recognition of Indigeneity within the governmental regulation of resource development. However, such recognition has been constrained. Witsuwit’en resistance to the Enbridge Northern Gateway Project highlights the ongoing emergence of Indigenous politics in excess of regulatory integration as traditional. This excess is continually reincorporated into colonial governance processes to resecure development, through not only techniques aimed at protecting Indigenous traditions but also training regimes designed to incorporate Indigenous labour within the industrial economy. Through the dissertation, I demonstrate the entanglement of resource development with a continuous cycle moving through moments of Indigenous contestation, colonial response, and subsequent Indigenous challenges. This cycle has relied on the exercise of sovereignty, disciplinarity, and governmentality as distinct yet interpenetrated modalities of colonial power. Colonial sovereignty operates to suspend the political ...